Composite piezoelectric photocatalyst as well as preparation method and application thereof

By introducing a composite structure of Ba(Ti0.80Zr0.20)O3-x(Ba0.7Ca0.3)TiO3 piezoelectric material and photoelectric semiconductor material into the photocatalyst, the problem of low catalytic efficiency and stability of existing piezoelectric photocatalysts is solved, and efficient degradation of organic pollutants and improvement of material stability is achieved.

CN119633793APending Publication Date: 2025-03-18GUANGDONG POLYTECHNIC NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411922449.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing piezoelectric photocatalysts have problems with low catalytic efficiency and stability, and it is difficult to effectively degrade organic pollutants.

Method used

A composite piezoelectric photocatalyst is used, which consists of a core and a surface layer, which comprises Ba(Ti0.80Zr0.20)O3-x(Ba0.7Ca0.3)TiO3 piezoelectric material, and the surface layer comprises a photoelectric semiconductor material. The polarized electric field of the piezoelectric material adsorbs free charges, forming hydroxyl groups and superoxide radicals, triggering a redox reaction, and by driving the reverse migration of photogenerated electron-hole pairs, inhibiting their recombination, thereby enhancing catalytic activity.

Benefits of technology

It achieves efficient degradation of organic pollutants, significantly improves catalytic activity, and protects piezoelectric materials through the semiconductor surface layer, improving the chemical stability of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633793A_ABST
    Figure CN119633793A_ABST
Patent Text Reader

Abstract

The invention relates to a composite piezoelectric photocatalyst and a preparation method and application thereof. The composite piezoelectric photocatalyst comprises a core and a surface layer at least partially coating the core, the core comprises a piezoelectric material, the chemical composition of the piezoelectric material is Ba (Ti0. 80Zr0. 20) O3-x (Ba0. 7Ca0. 3) TiO3, x represents the molar ratio of Ba (Ti0. 80Zr0. 20) O3 to (Ba0. 7Ca0. 3) TiO3, and x is greater than or equal to 0.4 and less than or equal to 0.6; the surface layer includes an optoelectronic semiconductor material. According to the composite piezoelectric photocatalyst, positive and negative free charges in the environment can be adsorbed through a polarized electric field of a piezoelectric material under the action of stress, hydroxyl and superoxide free radicals are further formed, a series of oxidation-reduction reactions are initiated, and organic pollutants are subjected to piezoelectric catalytic degradation. Meanwhile, a polarization electric field of the piezoelectric material can also inhibit recombination by driving photo-induced electron-hole pairs of the photocatalyst to reversely migrate, so that the photocatalytic activity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a composite piezoelectric photocatalyst and a preparation method and application thereof. Background Art

[0002] Photocatalysis is an advanced oxidation technology that can degrade organic pollutants into carbon dioxide and water. However, the high recombination rate of photogenerated electron-hole pairs during the migration process limits its catalytic activity.

[0003] Piezoelectric materials can be polarized under natural conditions to generate a built-in electric field. Piezoelectric materials have piezoelectricity and can be polarized and form electric dipoles in response to external stress or electric field. Studies have found that by introducing piezoelectric materials into photocatalytic systems, after compounding with semiconductors, the built-in electric field generated by their piezoelectric effect can drive the efficient separation of photogenerated carriers inside the semiconductor. However, piezoelectric photocatalysts currently still have relatively low catalytic efficiency or stability.

[0004] Therefore, there is an urgent need to develop related technologies and products with high-voltage electro-photocatalytic efficiency and excellent stability. Summary of the invention

[0005] Based on this, the present application provides a composite piezoelectric photocatalyst and a preparation method and application thereof, wherein the composite piezoelectric photocatalyst has high catalytic activity and stability.

[0006] The specific technical solutions are as follows:

[0007] On one hand, the present application provides a composite piezoelectric photocatalyst, the composite piezoelectric photocatalyst comprising a core and a surface layer at least partially covering the core;

[0008] The core comprises a piezoelectric material, the chemical composition of which is Ba(Ti 0.80 Zr 0.20 )O3-x(Ba 0.7 Ca 0.3 )TiO3, where x represents (Ba 0.7 Ca 0.3 )TiO3 and Ba(Ti 0.80 Zr 0.20 )O3 molar ratio, 0.4≤x≤0.6;

[0009] The surface layer comprises an optoelectronic semiconductor material.

[0010] The composite piezoelectric photocatalyst in the present application comprises a core and a surface layer, wherein the core comprises a piezoelectric material, and the piezoelectric material comprises Ba(Ti 0.80 Zr 0.20 )O3-x(Ba 0.7 Ca0.3 )TiO3, wherein 0.4≤x≤0.6; the surface layer includes semiconductor materials. Through the polarization electric field of the above-mentioned specific piezoelectric material under stress, it is possible to adsorb positive and negative free charges in the environment to form hydroxyl and superoxide radicals, and initiate a series of redox reactions to achieve piezoelectric catalytic degradation of organic pollutants. At the same time, the polarization electric field of the piezoelectric material can also enhance the photocatalytic activity of the semiconductor material by driving the reverse migration of photogenerated electron-hole pairs in the semiconductor material and inhibiting their recombination. Therefore, the constructed piezoelectric / semiconductor heterogeneous piezoelectric photocatalyst has significant synergistic catalytic activity. In addition, the semiconductor surface layer can protect the core of the piezoelectric material from erosion by the external environment, thereby improving the chemical stability of the material.

[0011] In some embodiments, the diameter of the core is 50 nm to 200 nm;

[0012] And / or, the thickness of the surface layer is 5 nm to 50 nm;

[0013] And / or, the core has the morphology of nanofibers or nanoparticles.

[0014] In some of the embodiments, the semiconductor material includes at least one of TiO2, ZnO, ZrO2, CeO2, ZnS and CdS.

[0015] In some embodiments, the molar ratio of the piezoelectric material to the semiconductor material is 1-10:1.

[0016] In some embodiments, the steps include:

[0017] Mixing raw materials for preparing the piezoelectric material to prepare a precursor solution; the raw materials for preparing the piezoelectric material include barium salt, calcium salt, zirconium salt and titanium salt;

[0018] Electrospinning and / or spraying the precursor solution, followed by drying and a first annealing treatment, to prepare a piezoelectric material;

[0019] After mixing the raw materials for preparing the piezoelectric material, the solvent and the semiconductor material for reaction, the reaction product is post-treated, and the post-treated reaction product is subjected to a second annealing treatment to prepare a composite piezoelectric photocatalyst;

[0020] The temperature of the first annealing treatment is different from the temperature of the second annealing treatment.

[0021] In some embodiments, the drying treatment temperature is 100° C. to 200° C., and the drying treatment time is 2 h to 8 h.

[0022] In some embodiments, the temperature of the first annealing treatment is 600° C. to 800° C., and the time of the first annealing treatment is 1 h to 8 h;

[0023] And / or, the temperature of the second annealing treatment is 450° C. to 550° C., and the time of the second annealing treatment is 1 hour to 3 hours.

[0024] In some embodiments, the solvent includes at least one of acetylacetone, ethylene glycol methyl ether, acetonitrile and ethanol.

[0025] In some embodiments, after the drying process and before the first annealing process, a grinding process is further included;

[0026] And / or, the post-treatment includes the steps of centrifuging and washing the reaction product in sequence.

[0027] The application of the composite piezoelectric photocatalyst in the degradation of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The microstructure characterization results of BTZ-xBTZ (x=0.4, 0.5, 0.6) nanofibers prepared in Example 1 are shown in FIG.

[0029] Figure 2 This is a graph showing the characterization results of the BTZ-xBTZ (x=0.4, 0.5, 0.6) nanofibers prepared in Example 1 using piezoelectric atomic force microscopy;

[0030] Figure 3 The scanning electron microscope results of the piezoelectric material and the composite piezoelectric photocatalyst prepared in Example 1 and Example 2;

[0031] Figure 4 X-ray diffraction patterns of the piezoelectric materials and composite piezoelectric photocatalysts prepared in Example 1 and Example 2;

[0032] Figure 5 is a transmission electron microscope image of the piezoelectric material and the composite piezoelectric photocatalyst prepared in Example 1;

[0033] Figure 6 is a transmission electron microscope image of the piezoelectric material and the composite piezoelectric photocatalyst prepared in Example 2;

[0034] Figure 7 The UV-visible spectrum analysis results of the piezoelectric material and composite piezoelectric photocatalyst prepared in Example 1 and Example 2 are shown. DETAILED DESCRIPTION

[0035] The following is a further detailed description of the composite piezoelectric photocatalyst and its preparation method and application of the present application in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0037] The optional scope of the terms "and / or", "or / and", and "and / or" used in this article includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, said any and all combinations include any combination of any two related listed items, any more related listed items, or all related listed items.

[0038] One embodiment of the present application provides a composite piezoelectric photocatalyst, the composite piezoelectric photocatalyst comprising a core and a surface layer at least partially covering the core;

[0039] The core comprises a piezoelectric material, the chemical composition of which is Ba(Ti 0.80 Zr 0.20 )O3-x(Ba 0.7 Ca 0.3 )TiO3, where x represents (Ba 0.7 Ca 0.3 )TiO3 and Ba(Ti 0.80 Zr 0.20 )O3 molar ratio, 0.4≤x≤0.6;

[0040] The surface layer comprises a photovoltaic semiconductor material.

[0041] The composite piezoelectric photocatalyst in the present application comprises a core and a surface layer, wherein the core comprises a piezoelectric material, and the piezoelectric material comprises Ba(Ti 0.80 Zr 0.20 )O3-x(Ba 0.7 Ca 0.3)TiO3, wherein 0.4≤x≤0.6; the surface layer includes semiconductor materials. Through the polarization electric field of the above-mentioned specific piezoelectric material under stress, it is possible to adsorb positive and negative free charges in the environment to form hydroxyl and superoxide radicals, and initiate a series of redox reactions to achieve piezoelectric catalytic degradation of organic pollutants. At the same time, the polarization electric field of the piezoelectric material can also enhance the photocatalytic activity of the semiconductor material by driving the reverse migration of photogenerated electron-hole pairs in the semiconductor material and inhibiting their recombination. Therefore, the constructed piezoelectric / semiconductor heterogeneous piezoelectric photocatalyst has significant synergistic catalytic activity. In addition, the semiconductor surface layer can protect the core of the piezoelectric material from erosion by the external environment, thereby improving the chemical stability of the material.

[0042] It should be noted that the value range of x is "0.4~0.6", for example, it can be 0.4, 0.5 or 0.6, or a range formed by any two of these point values ​​as end values.

[0043] It can be understood that when x=0.4, Ba(Ti 0.80 Zr 0.20 )O3 content is relatively high, which may cause the crystal structure of the material to be more inclined to a phase with higher symmetry. As x increases to 0.5, the composition of BCTZ changes, (Ba 0.7 Ca 0.3 )TiO3 may cause the distortion of the crystal structure and produce more lattice defects or grain boundaries. These defects and grain boundaries can serve as capture centers for photogenerated carriers, which is beneficial to improve the separation efficiency of photogenerated carriers and thus enhance the photocatalytic activity. When x=0.6, (Ba 0.7 Ca 0.3 )A further increase in the TiO3 content may make the crystal structure more complex, with more phase coexistence or phase transition phenomena. This complex crystal structure may lead to an enhancement of the local electric field, which is beneficial to the separation and transmission of photogenerated carriers, and may also improve the piezoelectric properties of the material. In addition, as x increases from 0.4 to 0.6, the band structure of the material may change, gradually enhancing its ability to absorb visible light, thereby improving the activity of the photocatalyst under visible light.

[0044] In some embodiments, the diameter of the core is 50nm~200nm, including but not limited to 50nm, 51nm, 52nm, 53nm, 54nm, 55nm, 56nm, 57nm, 58nm, 59nm, 60nm, 61nm, 62nm, 63nm, 64nm, 65nm, 66nm, 67nm, 68nm, 69nm, 70nm, 71nm, 72nm, 73nm, 74nm, 75nm, 76nm, 77nm, 78nm, 79nm, 80nm, 81nm, 82nm, 83nm, 84nm, 85nm, 86nm, 87nm, 88nm, 89nm, 90nm, 91nm, 92nm, 93nm, 94nm, 95nm, 96nm, 97nm, 98nm, 99nm, 100nm, 101nm, 102nm, 103nm, 104nm, 105nm, 106nm, 107nm, 108nm, 109nm, 110nm, 111nm, 112nm, 113nm, 114nm, 115nm, 116nm, 117nm, 118nm, 119n m, 120nm, 121nm, 122nm, 123nm, 124nm, 125nm, 126nm, 127nm, 128nm, 12 9nm, 130nm, 131nm, 132nm, 133nm, 134nm, 135nm, 136nm, 137nm, 138nm, 139nm, 140nm, 141nm, 142nm, 143nm, 144nm, 145nm, 146nm, 147nm, 148 nm, 149nm, 150nm, 151nm, 152nm, 153nm, 154nm, 155nm, 156nm, 157nm, 158nm, 159nm, 160nm, 161nm, 162nm, 163nm, 164nm, 165nm, 166nm, 167n 198nm, 200nm, 201nm, 202nm, 203nm, 204nm, 205nm, 206nm, 207nm, 208nm, 209nm, and in some examples the range can be composed of any two of these point values ​​as end values, the same below.

[0045] In one specific example, the diameter of the core is 55 nm.

[0046] In another specific example, the diameter of the core is 193 nm.

[0047] In some embodiments, the thickness of the surface layer is 5 nm~50 nm, including but not limited to 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 46 nm, 47 nm, 48 nm, 49 nm, and 50 nm.

[0048] It can be understood that the diameter of the core and the thickness of the surface layer are controlled within the above-mentioned specific ranges, which can shorten the migration path of photogenerated electron-hole pairs, significantly control the photocatalytic activity by inhibiting recombination, and increase the specific surface area of ​​the material, enhance the light absorption capacity, and more effectively absorb photon energy, thereby improving the efficiency of the photocatalytic reaction. For example, when photocatalytically degrading organic pollutants, more light energy can be absorbed to generate photogenerated carriers, accelerating the degradation reaction.

[0049] In some embodiments, the core is in the form of nanofibers or nanoparticles.

[0050] In some of the embodiments, the semiconductor material includes at least one of TiO2, ZnO, ZrO2, CeO2, ZnS and CdS.

[0051] In some embodiments, the molar ratio of the piezoelectric material to the semiconductor material is 1-10:1, including but not limited to 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, and 10:1.

[0052] In a specific example, the molar ratio of the piezoelectric material to the semiconductor material is 1:1.

[0053] Another embodiment of the present application provides a method for preparing a composite piezoelectric photocatalyst, comprising steps S10 to S30.

[0054] Step S10: Mix the raw materials for preparing the piezoelectric material to prepare a precursor solution.

[0055] In some embodiments, raw materials for preparing the piezoelectric material include barium salt, calcium salt, zirconium salt and titanium salt.

[0056] In one specific example, raw materials for preparing the piezoelectric material include barium acetate, calcium acetate hydrate, zirconium isopropoxide and tetrabutyl titanate.

[0057] Step S20: After electrospinning the precursor solution, sequentially perform drying treatment and a first annealing treatment to prepare a piezoelectric material.

[0058] In some embodiments, the temperature of the drying treatment is 100°C ~ 200°C, including but not limited to 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, and 200°C.

[0059] In some embodiments, the drying process is carried out at a temperature of 120°C to 200°C.

[0060] In some embodiments, the drying time is 2 h to 8 h, including but not limited to 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, and 8 h.

[0061] In a specific example, the drying process takes 4 hours.

[0062] In some embodiments, the temperature of the first annealing treatment is 600°C ~ 800°C, including but not limited to 600°C, 605°C, 610°C, 615°C, 620°C, 625°C, 630°C, 635°C, 640°C, 645°C, 650°C, 655°C, 660°C, 665°C, 670°C, 675°C, 680°C, 685°C, 690°C, 695°C, 700°C, 705°C, 710°C, 715°C, 720°C, 725°C, 730°C, 735°C, 740°C, 745°C, 750°C, 755°C, 760°C, 765°C, 770°C, 775°C, 780°C, 785°C, 790°C, 795°C, and 800°C.

[0063] It can be understood that by controlling the first annealing temperature within the above specific range, the crystal structure of the BCTZ piezoelectric material can be optimized, and the high temperature annealing process can cause the impurity atoms in the material to volatilize or undergo chemical reactions to form more stable compounds, and can also repair some lattice defects in the material. Controlling the first annealing temperature helps rearrange atoms to form a more regular and complete crystal structure, thereby enhancing the piezoelectric effect.

[0064] In a specific example, the temperature of the first annealing treatment is 750°C.

[0065] In some embodiments, the heating rate of the first annealing treatment is 1°C / min to 5°C / min, including but not limited to 1°C / min, 2°C / min, 3°C / min, 4°C / min, and 5°C / min.

[0066] In a specific example, the heating rate of the first annealing treatment is 2° C. / min.

[0067] In some embodiments, the first annealing treatment time is 1 hour to 8 hours, including but not limited to 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, and 8 hours.

[0068] In a specific example, the first annealing treatment lasts for 2 hours.

[0069] Step S30: After the raw materials for preparing the above-mentioned piezoelectric material, solvent and semiconductor material are mixed and reacted, the reaction product is post-treated, and the reaction product after the above-mentioned post-treatment is subjected to a second annealing treatment to prepare a piezoelectric photocatalyst; wherein the temperature of the first annealing treatment is different from the temperature of the second annealing treatment.

[0070] In some embodiments, the temperature of the second annealing treatment is 450°C~550°C, including but not limited to 450°C, 455°C, 460°C, 465°C, 470°C, 475°C, 480°C, 485°C, 490°C, 495°C, 500°C, 505°C, 510°C, 515°C, 520°C, 525°C, 530°C, 535°C, 540°C, 545°C, 550°C.

[0071] It can be understood that the conditions of the second annealing treatment are controlled within the above-mentioned specific range, which can be beneficial to the growth and crystallization of TiO2 crystals, and can transform the amorphous structure of TiO2 into a crystalline structure, forming a more regular crystal structure. In the application of the photoelectric synergistic effect, the tightly bound interface can make the charges generated by the piezoelectric material better interact with the photogenerated carriers in the photoelectric semiconductor, thereby improving the overall photoelectric-piezoelectric conversion efficiency.

[0072] In a specific example, the temperature of the second annealing process is 500°C.

[0073] In some of the embodiments, the heating rate of the second annealing treatment is 2°C / min to 10°C / min, including but not limited to 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min.

[0074] In a specific example, the heating rate of the second annealing treatment is 5° C. / min.

[0075] In some embodiments, the second annealing treatment time is 1 hour to 3 hours, including but not limited to 1 hour, 2 hours, and 3 hours.

[0076] In a specific example, the second annealing treatment lasts for 2 hours.

[0077] In some embodiments, the solvent includes at least one of acetylacetone, ethylene glycol methyl ether, acetonitrile and ethanol.

[0078] In some of the embodiments, after the drying process and before the first annealing process, a grinding process is further included.

[0079] In some embodiments, the post-treatment step includes sequentially centrifuging and washing the reaction product.

[0080] The preparation method of the composite piezoelectric photocatalyst is to composite the semiconductor material with the BCTZ lead-free piezoelectric material through relatively simple preparation processes such as electrospinning and spraying technology. These methods are simple to operate, low in cost, easy to achieve large-scale production, and are conducive to the practical application and promotion of such composite piezoelectric photocatalysts.

[0081] The present application also provides an application of the above composite piezoelectric photocatalyst in degrading organic pollutants.

[0082] The above-mentioned piezoelectric photocatalyst has the ability to catalytically degrade organic pollutants, and its piezoelectric catalytic efficiency, photocatalytic efficiency and piezoelectric photocatalytic efficiency are all high, and can be widely used in the fields of environmental governance and ecological restoration.

[0083] The following are specific embodiments

[0084] The present application is further described below in conjunction with the accompanying drawings and embodiments, but the protection content of the present application is not limited to the scope described in the embodiments.

[0085] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, biological materials, etc. used in the following examples are all commercially available unless otherwise specified.

[0086] Example 1

[0087] 1. Selection and verification of piezoelectric materials

[0088] 1.1 Preparation of BTZ-xBTZ (x=0.4, 0.5, 0.6) nanofibers

[0089] A series of piezoelectric nanofibers were prepared at the quasi-isotropic phase boundary by using the sol-gel method combined with electrospinning technology.

[0090] The results are as follows Figure 1 As shown, Figure 1 BTZ-xBTZ (x=0.4, 0.5, 0.6) nanofibers were prepared by electrospinning technology, and the microstructure was characterized by (d, e, f), selected electron diffraction was characterized by (g, h, i), and the interplanar spacing of the nanocrystals was characterized by (j, k, l).

[0091] The piezoelectric atomic force microscopy technique was further used to characterize the piezoelectric properties of BTZ-xBTZ (x=0.4, 0.5, 0.6) nanofibers and the temperature-dependent Raman spectrum to screen out BCTZ nanofibers with higher piezoelectricity and phase transition temperature, such as Figure 2 As shown, Figure 2 . (a, b, c) displacement-voltage and phase-voltage diagrams, (d, e, f) temperature-dependent Raman spectra of BTZ-xBTZ (x=0.4, 0.5, 0.6) piezoelectric nanofibers; (g, h, i) Raman spectra and (j, k, l) intensity variation with temperature of E(LO+TO), B1 and E(TO), A1(TO).

[0092] The results show that BCTZ (x=0.5) nanofibers have a high piezoelectric coefficient of 136 pm V -1 and indoor temperature (260ºC).

[0093] 2. Preparation of composite piezoelectric photocatalyst

[0094] 2.1 Synthesis of BCTZ precursor metal ion solution using sol-gel method

[0095] First, acetylacetone and ethylene glycol methyl ether were mixed and stirred in a 50 ml blue-mouth bottle at a volume ratio of 5:1.3 for 4 hours, and then 2.17 g of barium acetate was dissolved in 20 ml of glacial acetic acid solution and magnetically stirred at 80° C. for 4 hours.

[0096] After cooling, add 0.26 g of calcium acetate monohydrate and stir at room temperature for 30 minutes. After it is completely dissolved, add 0.39 g of zirconium isopropoxide and stir at room temperature for 2 hours. Then add the prepared 5:1.3 mixed solution of acetylacetone and ethylene glycol methyl ether to make the volume 50 ml.

[0097] Finally, 3.06 g of tetrabutyl titanate was added and stirred at room temperature for 12 hours to obtain a transparent orange-yellow BCTZ precursor metal ion solution.

[0098] 2.2 Preparation of BCTZ nanofiber core by electrospinning

[0099] Nanofiber preparation was carried out at 15 kV by adding 3 g of PVP (K 30 , Mw ~4000) to increase the viscosity of the solution and prepare a precursor mixture.

[0100] The precursor mixture prepared above was loaded into a 10 ml plastic syringe and connected to a stainless steel needle G21. The gap between the needle tip and the collector (aluminum foil) was 15 cm, the feed rate was 0.3 ml per hour, and the relative humidity was kept below 30%. The spinning precursor BCTZ nanofibers were dried at 200 ° C for 4 hours, and then annealed at 750 ° C at 2 degrees Celsius per minute for 2 hours to obtain a BCTZ nanofiber core with a diameter of 55 nanometers.

[0101] 2.3 Construction of composite piezoelectric photocatalysts by wet chemical coating of TiO2 layers

[0102] First, 180 ml of acetonitrile solution and 60 ml of ethanol solution were mixed, and then 50 mg of BCTZ nanofibers were added and dissolved by ultrasonication. Then, 0.8 ml of tetrabutyl titanate and 5 ml of ethanol mixed solution were dripped at a flow rate of 0.5 ml / min.

[0103] The mixed solution was centrifuged, washed twice with deionized water and ethanol, and then the collected product was annealed at 500 degrees Celsius for 2 hours with a heating and cooling rate of 5 degrees Celsius per minute. Finally, a BCTZ@TiO2 composite piezoelectric photocatalyst with a surface layer of 7.5 nm was obtained, namely, BCTZ@TiO2 core-shell structured nanofibers with a diameter of 70 nanometers.

[0104] Example 2

[0105] The preparation method of the composite piezoelectric photocatalyst in Example 2 is basically the same as that in Example 1, except that: in the preparation of the piezoelectric material, agate grinding body needs to be used for grinding before and after the first annealing, and the other preparation conditions are the same as those in Example 1. The specific preparation method is as follows:

[0106] 2. Preparation of composite piezoelectric photocatalyst

[0107] 2.1 The BCTZ precursor metal ion solution was synthesized by the sol-gel method:

[0108] First, acetylacetone and ethylene glycol methyl ether were mixed and stirred in a 50 ml blue-mouth bottle at a volume ratio of 5:1.3 for 4 hours, and then 2.17 g of barium acetate was dissolved in 20 ml of glacial acetic acid solution and magnetically stirred at 80° C. for 4 hours.

[0109] After cooling, add 0.26 g of calcium acetate monohydrate and stir at room temperature for 30 minutes. After it is completely dissolved, add 0.39 g of zirconium isopropoxide and stir at room temperature for 2 hours. Then add the prepared 5:1.3 mixed solution of acetylacetone and ethylene glycol methyl ether to make the volume 50 ml.

[0110] Finally, 3.06 g of tetrabutyl titanate was added and stirred at room temperature for 12 hours to obtain a transparent orange-yellow BCTZ precursor metal ion solution.

[0111] 2.2 Preparation of BCTZ nanoparticles by electrospinning:

[0112] Nanofiber preparation was carried out at 15 kV by adding 3 g of PVP (K 30 , M w ~4000) to increase the viscosity of the solution and prepare a precursor mixture.

[0113] The prepared precursor mixture was loaded into a 10 ml plastic syringe and connected to a stainless steel needle G21. The gap between the needle tip and the collector (aluminum foil) was 15 cm, the feed rate was 0.3 ml per hour, and the relative humidity was kept below 30%. The spinning precursor BCTZ nanofibers were dried at 200 ° C for 4 hours, ground with an agate grinder, and then annealed at 750 ° C at 2 ° C per minute for 2 hours to obtain a BCTZ nanoparticle core with a diameter of 193 nm.

[0114] 2.3 Construction of composite piezoelectric photocatalysts by wet chemical coating of TiO2 layers

[0115] First, 180 ml of acetonitrile solution and 60 ml of ethanol solution were mixed, and then 50 mg of BCTZ nanoparticles were added and dissolved by ultrasonication. Then, 0.8 ml of tetrabutyl titanate and 5 ml of ethanol mixed solution were dripped at a flow rate of 0.5 ml / min.

[0116] The mixed solution was centrifuged, washed twice with deionized water and ethanol, and then the collected product was annealed at 500 degrees Celsius for 2 hours with a heating and cooling rate of 5 degrees Celsius per minute. Finally, a BCTZ@TiO2 composite piezoelectric photocatalyst with a surface layer of 37.5 nm was obtained, that is, BCTZ@TiO2 core-shell structured nanoparticles with a diameter of 268 nanometers.

[0117] test:

[0118] 1. The composite piezoelectric photocatalyst prepared in the above example was tested by scanning electron microscopy.

[0119] Figure 3 (a) and Figure 3 (b) are respectively a BCTZ nanofiber core with a diameter of 55 nanometers and a BCTZ nanoparticle core with a diameter of 193 nanometers prepared by electrospinning and spraying technology of the present invention, and the enlarged image thereof is shown in FIG. Figure 3 (c) and Figure 3 As shown in (d) in .

[0120] Figure 3 (e) and Figure 3 (f) is a BCTZ@TiO2 core-shell structure nanofiber with a diameter of 70 nanometers and a core-shell structure nanoparticle with a diameter of 268 nanometers prepared by coating a layer of TiO2 on the surface of the BCTZ nanofiber core and particle core by wet chemical method. The enlarged image is shown in Figure 3 (g) and Figure 3 As shown in (h) in .

[0121] 2. The composite piezoelectric photocatalyst prepared in the above example was characterized by an X-ray diffractometer.

[0122] Figure 4 X-ray diffraction patterns of BCTZ nanofiber cores and particle cores, BCTZ@TiO2 core-shell structured nanofibers and particles. The diffraction patterns of BCTZ nanofibers and particles contain a group of diffraction peaks, which are perovskite structures. The diffraction patterns of BCTZ@TiO2 core-shell structured nanofibers and particles contain two groups of diffraction peaks, which are perovskite structures and anatase structures, respectively, indicating that ferroelectric and optoelectronic semiconductor composite materials have been successfully prepared.

[0123] 3. The composite piezoelectric photocatalyst prepared in the above example was tested by transmission electron microscopy.

[0124] First, the basic microstructure was observed. The fiber sample was composed of tiny grains. Then, selected area electron diffraction was used to observe its microscopic crystal structure. The results showed that the grains that made up the fiber were mostly complete single crystal grains. Finally, the element surface was scanned on a single sample to prove that various elements were evenly distributed in the fiber. The Ti element in BCTZ@TiO2 was larger than the appearance of the BCTZ fiber, indicating that the core-shell structure nanofiber was successfully synthesized.

[0125] The results are as follows Figure 5 As shown, Figure 5 (a) and Figure 5 (b) in the figure are transmission electron micrographs of the BCTZ nanofiber core and BCTZ@TiO2 core-shell structure nanofiber in Example 1, the corresponding selected area electron diffraction patterns (c) and (d), and transmission electron micrographs (a1, b1) annular dark field, (a2, b2) Ba, (a3, b3) Ca, (a4, b4) Ti, and (a5, b5) Zr elemental surface scanning. The BCTZ nanofiber is composed of particles with a particle size of about 10 nanometers, and after being plated with TiO2, its surface layer is composed of fine nanoparticles of 7.5 nm. Figure 5 (c) and Figure 5(d) in the figure are selected area electron diffraction patterns. It can be seen from the figure that the (100) and (111) crystal planes correspond to the BCTZ of the perovskite structure, and the (010) and (004) crystal planes correspond to anatase TiO2. The corresponding transmission electron microscopy elemental scanning Figure 5 It can be seen from (a1-a5) and (b1-b5) that after the TiO2 layer is plated on the outside of the BCTZ nanofibers, the content of the Ti element shows a slight increase, and the contents of the Ca and Zr elements show a slight decrease, indicating that the BCTZ@TiO2 core-shell structured nanofiber piezoelectric photocatalyst has been successfully prepared.

[0126] Figure 6 (a) and Figure 6 (b) in the figure are transmission electron micrographs of the BCTZ nanoparticle core and BCTZ@TiO2 core-shell structure nanoparticles in Example 2, the corresponding selected area electron diffraction patterns (c) and (d), and transmission electron micrographs (a1, b1) annular dark field, (a2, b2) Ba, (a3, b3) Ca, (a4, b4) Ti, and (a5, b5) Zr elemental surface scanning. The BCTZ nanoparticles are spherical and composed of fine particles. After being plated with TiO2, the surface layer is fine nanoparticles. Figure 6 (c) and Figure 6 (d) in the figure are selected area electron diffraction patterns. It can be seen from the figure that the (111), (200) and (211) crystal planes correspond to the BCTZ of the perovskite structure, and the (010), (004) and (200) crystal planes correspond to anatase TiO2. The corresponding transmission electron microscopy elemental scanning Figure 6 It can be seen from (a1-a5) and (b1-b5) that after the TiO2 layer is plated on the outside of the BCTZ nanoparticles, the content of the Ti element shows a slight increase, and the contents of the Ca and Zr elements show a slight decrease, indicating that the BCTZ@TiO2 core-shell structured nanoparticle piezoelectric photocatalyst has been successfully prepared.

[0127] 4. The composite piezoelectric photocatalyst prepared in the above example was subjected to UV-visible spectroscopy analysis.

[0128] The results are as follows Figure 7 As shown, Figure 7 Piezoelectric catalytic UV-visible spectroscopic analysis of BCTZ nanofibers (a) and particles (b); (c, d) piezoelectric catalytic, (e, f) photocatalytic and (g, h) piezoelectric photocatalytic UV-visible spectroscopic analysis of BCTZ@TiO2 core-shell structure nanofibers and particles, respectively. The corresponding (i) degradation rate, (j) change in pollutant concentration, (k) catalytic degradation rate k value and (l) histogram distribution.

[0129] Figure 7(a, b) are the piezoelectric catalytic UV-visible spectroscopic analysis diagrams of BCTZ nanofiber core and particle core, respectively, indicating that the catalytic performance of BCTZ nanofiber with higher piezoelectric coefficient is better than that of nanoparticles. Figure 7 (c, d) are the piezoelectric catalytic UV-visible spectroscopic analysis diagrams of BCTZ@TiO2 core-shell structured nanofibers and particles, respectively. BCTZ@TiO2 core-shell structured nanofibers have high piezoelectric catalytic performance. Figure 7 (e, f) are the photocatalytic UV-visible spectroscopic analyses of BCTZ@TiO2 core-shell structured nanofibers and particles, respectively. Their catalytic degradation efficiencies are the same, but slightly less than piezoelectric catalysis.

[0130] Figure 7 (g, h) are the piezoelectric photocatalytic UV-visible spectra of BCTZ@TiO2 core-shell structure nanofibers and particles. The piezoelectric photocatalytic synergistic effect can significantly improve the catalytic efficiency, and the catalytic efficiency of the fiber is slightly higher than that of the particle. The corresponding degradation rate and pollutant concentration change with time are shown in Figure 2. Figure 7 As shown in (i, j) in . Figure 7 The catalytic degradation rate k value is calculated by (k) in the figure, and its size is distributed in columns from small to large. Figure 7 In (l).

[0131] The catalytic efficiency can be obtained by comparing the UV-visible absorption curves of MO in different catalytic stages, as shown in Equation 1. C0 and C represent the initial concentration and the instantaneous concentration in the catalytic stage, respectively.

[0132] (1)

[0133] The kinetic model of its catalytic rate is inversely proportional to the concentration of the reactants, as shown in Formula 2. t represents the reaction time.

[0134] (2)

[0135] Based on Formula 2, the catalytic rate constant k can be obtained from Formula 3.

[0136] (3)

[0137] The piezoelectric photocatalytic degradation rate constant of BCTZ@TiO2 core-shell structured nanofibers is 7.7×10 -2 min -1 , which is larger than 4.6×10 of BCTZ@TiO2 core-shell structure nanoparticles. -2 min -1 , and their respective photocatalytic (3.6×10 -2 min-1 , 3.6×10 -2 min -1 ) and piezocatalysis (4.5×10 -2 min -1 , 4.3×10 -2 min -1 ), and BCTZ nanofibers (3.3×10 -2 min -1 ) and nanoparticles (2.7×10 -2 min -1 ) of piezoelectric catalysis.

[0138] In summary, the TiO2 layer was coated on the surface of BCTZ nanofibers and particles prepared by electrospinning and spraying technology using a wet chemical method to synthesize BCTZ@TiO2 core-shell structured nanofibers and particles, which have good piezoelectric photocatalytic performance and are a piezoelectric photocatalyst with high catalytic efficiency, and can be widely used in the fields of environmental governance and ecological restoration.

[0139] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0140] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be based on the attached claims.

Claims

1. A composite piezoelectric photocatalyst, characterized in that: The composite piezoelectric photocatalyst comprises a core and a surface layer at least partially covering the core; The core includes a piezoelectric material, and the piezoelectric material includes Ba(Ti 0.80 Zr 0.20 )O3-x(Ba 0.7 Ca 0.3 )TiO3, where x represents (Ba 0.7 Ca 0.3 )TiO3 and Ba(Ti 0.80 Zr 0.20 )O3 molar ratio, 0.4≤x≤0.6; The surface layer includes a semiconductor material.

2. The composite piezoelectric photocatalyst according to claim 1, characterized in that The diameter of the core is 50nm~200nm; And / or, the thickness of the surface layer is 5nm~50nm; And / or, the core has the morphology of nanofibers or nanoparticles.

3. The composite piezoelectric photocatalyst according to claim 1, characterized in that The semiconductor material includes at least one of TiO2, ZnO, ZrO2, CeO2, ZnS and CdS.

4. The composite piezoelectric photocatalyst according to any one of claims 1 to 3, characterized in that The molar ratio of the piezoelectric material to the semiconductor material is 1-10:

1.

5. A method for preparing a composite piezoelectric photocatalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing raw materials for preparing the piezoelectric material to prepare a precursor solution; the raw materials for preparing the piezoelectric material include barium salt, calcium salt, zirconium salt and titanium salt; Electrospinning and / or spraying the precursor solution, followed by drying and a first annealing treatment, to prepare a piezoelectric material; After mixing the raw materials for preparing the piezoelectric material, the solvent and the semiconductor material for reaction, the reaction product is post-treated, and the post-treated reaction product is subjected to a second annealing treatment to prepare a composite piezoelectric photocatalyst; The temperature of the first annealing treatment is different from the temperature of the second annealing treatment.

6. The method for preparing the composite piezoelectric photocatalyst according to claim 5, characterized in that: The temperature of the drying treatment is 100° C. to 200° C., and the time of the drying treatment is 2 h to 8 h.

7. The method for preparing the composite piezoelectric photocatalyst according to claim 5, characterized in that: The temperature of the first annealing treatment is 600° C. to 800° C., and the time of the first annealing treatment is 1 h to 8 h; And / or, the temperature of the second annealing treatment is 450° C. to 550° C., and the time of the second annealing treatment is 1 hour to 3 hours.

8. The method for preparing the composite piezoelectric photocatalyst according to claim 5, characterized in that: The solvent includes at least one of acetylacetone, ethylene glycol methyl ether, acetonitrile and ethanol.

9. The method for preparing the composite piezoelectric photocatalyst according to any one of claims 5 to 8, characterized in that: After the drying process and before the first annealing process, a grinding process is also included; And / or, the post-treatment includes the steps of centrifuging and washing the reaction product in sequence.

10. Use of the composite piezoelectric photocatalyst according to any one of claims 1 to 4 in degrading organic pollutants.

Citation Information

Cited By

  • A nitrogen-doped zinc sulfide piezocatalyst rich in sulfur vacancies and a preparation method and application thereof

    CN122702472A